The Betty & Barney Hill alien abduction - Bowman, Chris (2020)
"Exciting illustrations follow the events of the Betty and Barney Hill alien abduction. The combination of brightly colored panels and leveled text is intended for students in grades 3 through 7"--
An interrupted journey -- Missing time -- Trying to remember -- Believers and skeptics -- Theories behind the abduction.
Includes bibliographical references and index.
Grade: 3 to 7.
Keywords: Hill, Betty -- Juvenile literature; Hill, Barney, -- 1922-1969 -- Juvenile literature; Alien abduction -- New Hampshire -- Juvenile literature; Unidentified flying objects -- Sightings and encounters -- New Hampshire -- Juvenile literature